Analisis Strategi Pemasaran Pantai Natsepa Dalam Mendukung Pengembangan Pariwisata Berbasis Masyarakat - Yoan Pattiselanno; Olivia Tahalele (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
Analysis of the Marketing Strategy of Natsepa Beach in Supporting Community-Based Tourism Development. Supervisor I: Sandra I. Telussa, and Supervisor II: Olivia Tahalele. Natsepa Beach is a leading tourist destination in Central Maluku Regency that has great potential for the development of nature-based and culinary tourism. This beach is known not only for its natural beauty but also for Rujak Natsepa, which has become a local culinary icon. The combination of beach tourism and culinary tourism serves as the main strength in building the destination’s image. The management of Natsepa Beach is carried out by the Central Maluku Tourism Office with the involvement of the local community, particularly MSME actors and rujak vendors. Community involvement is important because the tourism sector contributes to the economy of local residents. The local government also provides guidance regarding hygiene and serving standards to maintain the quality of local products and the image of the tourist destination. The current marketing strategy of Natsepa Beach utilizes digital media and social media through accounts such as Pesona Maluku Tengah, as well as support from influencers and content creators. Promotion does not only highlight the beach scenery but also tourism activities and Natsepa’s distinctive culinary attractions. However, the absence of an official account dedicated specifically to Natsepa Beach means that promotional information is still combined with information about other destinations. From the perspective of Integrated Marketing Communication (IMC), the marketing of Natsepa Beach includes six main components, namely advertising, sales promotion, public relations, personal selling, direct marketing, and internet marketing. The implementation of these IMC components strengthens the branding of Natsepa Beach as a distinctive natural and culinary tourism destination and supports the economic growth of the local community.